First-principles investigation of the electrocatalytic reduction of CO2 on zirconium-based single-, double-, and triple-atom catalysts anchored on a graphitic carbon nitride monolayer - Hassan, Afshana; Anis, Insha; Shafi, Sadaf; Assad, Assif; Rasool, Anjumun; Khanam, Romana; Bhat, Gulzar Ahmad; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (ACS Applied Nano Materials, 2022)
Conversion of carbon dioxide (CO2) with the help of an appropriate electrocatalyst with high stability, low onset potential, and exceptional selectivity is still one of the great tasks in the electrocatalytic reduction of CO2 to valuable chemicals. Herein, by means of systematic first-principles simulations, we investigate the CO2 reduction reaction (CO2RR) activity of zirconium-based single-, double-, and triple-atom (Zrn@C2N; n = 1-3) catalysts anchored on a graphitic carbon-nitride monolayer. In tune with the Sabatier principle, our results reveal that a moderate CO2 binding is vital for a low onset potential for the CO2RR. Consequently, based on rigorous free energy calculations, the Zr-based single-atom catalyst (SAC) is found to be most effective to convert CO2 to valuable products such as HCOOH and CH3OH. It is worth noting that CO2 reduction to HCOOH is spontaneous via the *HCOO intermediate on Zr1@C2N and involves a low onset potential of -0.23 V with respect to the reversible hydrogen electrode from the *COOH intermediate. Among all the catalysts evaluated computationally, the Zr SAC further reveals the lowest onset potential of -0.89 V for CH3OH formation. The results show that the Zr-based catalysts especially Zr1@C2N are found to effectively suppress the competitive hydrogen evolution reaction and promote the CO2RR. Moreover, all three catalysts exhibit high kinetic and thermal stability with negligible distortion due to which their structures can be retained very well up to 600 K. Thus, the current work may provide effective catalyst-design strategies for enhancing the electrocatalytic CO2RR performance of Zr-based materials.
Keywords: C1 and C2 products; CO2 reduction; first-principles simulations; hydrogen evolution reaction; onset potential; single-atom catalysts (SACs); Zrn@C2N catalysts

Tantalum based single, double, and triple atom catalysts supported on g-C2N monolayer for effective nitrogen reduction reaction: a comparative DFT investigation - Rasool, Anjumun; Anis, Insha; Dixit, Mudit; Maibam, Ashakiran; Hassan, Afshana; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Catalysis Science & Technology, 2022)
Design of efficient and low cost electrocatalysts for the reduction of N-2 molecule to NH3 in a green manner remains a great challenge in the 21st century. Herein, we have used density functional theory based first principle simulations to systematically investigate the nitrogen reduction reaction (NRR) ability of single, double, and triple Ta-atom catalysts anchored to C2N monolayer. Our results demonstrate that the single and triple Ta-atom catalysts anchored to C2N monolayer act as superior catalysts for the NRR via alternating and distal pathways as compared to the Ru(0001) stepped surface. In particular, the triple Ta-atom catalyst anchored to C2N shows enhanced NRR performance with a limiting potential of -0.72 V which is comparable to the experimentally reported Ru based single atom catalyst. Further, all the three catalysts were found to be highly selective for NRR with an enhanced ability to suppress the competitive hydrogen evolution reaction. Electronic structure analysis revealed that the enhanced ability of Ta-3@C2N catalyst to effectively capture and reduce N-2 molecule could be attributed to the built up of localized d states near the fermi level, thereby aiding in strong electron transfer into the antibonding orbitals of N-2. Thus, our findings propose a highly active catalyst for the NRR with an emphasis on the importance of triple atom-based catalysts for electrocatalytic applications.